Amphibian secretions for drug discovery studies: A search for new antiparasitic and antifungal compounds - Tempone, André Gustavo; Melhem, Márcia de Souza Carvalho; Prado, Frederico Oliveira; Motoie, Gabriela; Hiramoto, Roberto Mitsuyoshi; Antoniazzi, Marta Maria; Haddad, Celio Fernando Baptista [UNESP]; Jared, Carlos (Elsevier, 2007)
The antiparasitic and antifungal activities of nine amphibian skin secretions were studied in different in vitro models. Seven secretions presented a considerable antiprotozoan activity and one showed promising results against Candida sp. These results can be the basis for the development of new drugs, especially for neglected parasitic diseases. © 2007 Bentham Science Publishers Ltd.
Keywords: Amphibians; Antimicrobial; Leishmania; Peptides; Secretions; Trypanosoma; amino acid oxidase; amphibian protein; antifungal agent; antiparasitic agent; benznidazole; meglumine antimonate; pentamidine; pyrimethamine; Amphibia; animal cell; animal experiment; animal model; animal tissue; Candida; controlled study; dose response; drug design; drug effect; drug research; enzyme activity; growth inhibition; mouse; nonhuman; priority journal; skin secretion